Almost everywhere convergence of two-dimensional Walsh-Nörlund means - Goginava, U.; Nagy, K. (Carpathian Mathematical Publications, 2024)
The present paper the almost everywhere convergence of two-dimensional Walsh-Nörlund means is studied, when the given function belongs to the hybrid Hardy space $H_{ atural}$. Because the Nörlund means are a generalization of several known classical summability methods, previously known classical theorems are derived from the main theorem. In addition some new results follow in particular cases as well.